Severe Aplastic Anemia following Parvovirus B19-Associated Acute Hepatitis - Masanori Furukawa; Kosuke Kaji; Hiroyuki Masuda; Kuniaki Ozaki; Shohei Asada; Aritoshi Koizumi; Takuya Kubo; Norihisa Nishimura; Yasuhiko Sawada; Kosuke Takeda; Tsuyoshi Mashitani; Masayuki Kubo; et al. (Case Reports in Hepatology)
Human parvovirus (HPV) B19 is linked to a variety of clinical manifestations, such as erythema infectiosum, nonimmune hydrops fetalis, and transient aplastic anemia. Although a few cases have shown HPVB19 infection as a possible causative agent for hepatitis-associated aplastic anemia (HAAA) in immunocompetent patients, most reported cases of HAAA following transient hepatitis did not have delayed remission. Here we report a rare case of severe aplastic anemia following acute hepatitis with prolonged jaundice due to HPVB19 infection in a previously healthy young male. Clinical laboratory examination assessed marked liver injury and jaundice as well as peripheral pancytopenia, and bone marrow biopsy revealed severe hypoplasia and fatty replacement. HPVB19 infection was diagnosed by enzyme immunoassay with high titer of anti-HPVB19 immunoglobulin M antibodies. Immunosuppressive therapy was initiated 2 months after the onset of acute hepatitis when liver injury and jaundice were improved. Cyclosporine provided partial remission after 2 months of medication without bone marrow transplantation. Our case suggests that HPVB19 should be considered as a hepatotropic virus and a cause of acquired aplastic anemia, including HAAA.